2019
DOI: 10.1001/jamanetworkopen.2019.6961
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preterm Birth and Low Birth Weight With Romantic Partnership, Sexual Intercourse, and Parenthood in Adulthood

Abstract: Key Points Question Are adults who were born preterm or with low birth weight less likely to experience social transitions normative of adulthood, such as romantic partnerships, sexual intercourse, or parenthood? Findings In this systematic review and meta-analysis of 21 studies describing up to 4.4 million participants, adults who were born preterm or with low birth weight were less likely to experience a romantic partnership, sexual intercourse, or parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 72 publications
0
54
3
1
Order By: Relevance
“…It would also be interesting to study why, despite their evident neonatal medical struggles and proven educational and social problems, there is no conclusive evidence that the HRQoL of those born VPT or VLBW in adulthood is affected. This is all the more challenging in the light of recent findings that VPT/VLBW subjects lagged behind their term‐born peers in related areas of long‐term psychosocial outcome, such as wealth 44 and engagement in romantic partnership and sexual intercourse 45 …”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to study why, despite their evident neonatal medical struggles and proven educational and social problems, there is no conclusive evidence that the HRQoL of those born VPT or VLBW in adulthood is affected. This is all the more challenging in the light of recent findings that VPT/VLBW subjects lagged behind their term‐born peers in related areas of long‐term psychosocial outcome, such as wealth 44 and engagement in romantic partnership and sexual intercourse 45 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies revealed that LBW affects adulthood social relationships and lower educational qualifications, decreased rate of employment, and increased rate of receipt of social benefits in adulthood [65,66], disability [67], and common chronic health conditions [68]. A systematic review and meta-analysis supported that adults born with LBW were less likely to have ever experienced a romantic partnership, to have had sexual intercourse to have become parents (OR) [66]. This might be due to the lack of sexual or partner relationships that might increase the risk of decreased well-being and poorer physical and mental health and subsequent psychiatric disorders.…”
Section: Adverse Perinatal Outcomes Of Low Birth Weightmentioning
confidence: 99%
“…Of notice, large Scandinavian register studies have shown that individuals born preterm or with low birthweight were less likely to ever be in a registered partnership or to become parents (39,48). Other authors have also found that ABP, with or without impairments, were more likely to be single compared to term born peers (27) and that adults born preterm or with low birthweight were less likely to experience a romantic partnership, sexual intercourse, or parenthood than their peers who were born full-term (49).…”
Section: Discussionmentioning
confidence: 99%